Three new species of the Neotropical genus Phyllotingis (Hemiptera: Heteroptera: Aradidae) - Heiss, Ernst (Zootaxa, 2018)
Three new species of Phyllotingis Walker, 1873 (Hemiptera: Heteroptera: Aradidae), Ph. tortugueria sp. nov. and Ph. costaricana sp. nov.from Costa Rica (representing a new generic record for the country), and Ph. moraguesi sp.nov. from French Guyana are described and illustrated. A key to all species of Phyllotingis is presented.